New sesquiterpene dilactone and β-carboline alkaloid and the α-glucosidase inhibitory activity of selected phytochemicals from Neolitsea cassia (L.) Kosterm - Jani, Nor Akmalazura; Sirat, Hasnah Mohd; Ahmad, Farediah; Aminudin, Nurul Iman (Taylor & Francis, 2021)
One new sesquiterpene dilactone, coccinine (1) and one new b-carboline alkaloid, daibucarboline F (2) together with 10 known compounds; linderane (3), linderalactone (4), pseudoneolinderane (5), linderanlide C (6), linderanine A (7), epicatechin (8), ()-taxifolin (9), astilbin (10), L-quercitrin (11) and afzelin (12) were isolated from the stems and leaves of Neolitsea cassia (L.) Kosterm (Lauraceae). The structures of (1 and 2) were established by extensive spectroscopic methods and the known compounds were identified by comparisons with data reported in literature. The relative stereochemistry of compound (1) was assigned by Xray diffraction analysis with Cu-Ka irradiation. Compounds (3-8) and (10) were evaluated for their a-glucosidase enzymatic inhibitory activity. Compounds (4-6), (8) and (10) exhibited inhibition towards a-glucosidase enzymatic activity with IC50 values ranging from 12.10 to 96.77 lM. This is the first report on the isolation of phytochemicals from N. cassia and their bioactivities.